Additive manufacturing of mechanochromic polycaprolactone on entry-level systems. Issue 5 (17th August 2015) - Eujin Pei, Dr; Peterson, Gregory I.; Yurtoglu, Mete; Larsen, Michael B; Craig, Stephen L.; Ganter, Mark A.; Storti, Duane W.; Boydston, Andrew J.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to explore and demonstrate the ability to integrate entry-level additive manufacturing (AM) techniques with responsive polymers capable of mechanical to chemical energy transduction. This integration signifies the merger of AM and smart materials. Design/methodology/approach – Custom filaments were synthesized comprising covalently incorporated spiropyran moieties. The mechanical activation and chemical response of the spiropyran-containing filaments were demonstrated in materials that were produced via fused filament fabrication techniques. Findings – Custom filaments were successfully produced and printed with complete preservation of the mechanochemical reactivity of the spiropyran units. These smart materials were demonstrated in two key constructs: a center-cracked test specimen and a mechanochromic force sensor. The mechanochromic nature of the filament enables (semi)quantitative assessment of peak loads based on color change, without requiring any external analytical techniques. Originality/value – This paper describes the first examples of three-dimensional-printed mechanophores, which may be of significant interest to the AM community. The ability to control the chemical response to external mechanical forces, in combination with AM to process the bulk materials, potentiates customizability at the molecular and macroscopic length scales.